First description of the female of Arrenurus nagysalloensis szalay (Acari, hydrachnidia) - Esen, Yunus; Mart, Abdullah; Erman, Orhan (Tyumen State University, 2017)
In this study, the female of Arrenurus (Truncaturus) nagysalloensis Szalay, 1934 is described for the first time from Elazığ Province, Turkey. © Acarina 2017
Keywords: Arrenurus nagysalloensis; Description; Female morphology; Hydrachnidia; Turkey